2022
DOI: 10.3389/fimmu.2022.867962
|View full text |Cite
|
Sign up to set email alerts
|

HSV-2-Specific Human Female Reproductive Tract Tissue Resident Memory T Cells Recognize Diverse HSV Antigens

Abstract: Antigen-specific TRM persist and protect against skin or female reproductive tract (FRT) HSV infection. As the pathogenesis of HSV differs between humans and model organisms, we focus on humans with well-characterized recurrent genital HSV-2 infection. Human CD8+ TRM persisting at sites of healed human HSV-2 lesions have an activated phenotype but it is unclear if TRM can be cultivated in vitro. We recovered HSV-specific TRM from genital skin and ectocervix biopsies, obtained after recovery from recurrent geni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 113 publications
0
5
0
Order By: Relevance
“…We then assayed the respective short-term TG-TCL for IFNγ secretion in response to incubation with the HLA-I matched aAPC. We have previously applied this platform to uncover the targets and diversity of HSV- and VZV-specific T-cells in human blood and other tissues in an unbiased way [ 16 , 19 , 25 27 ]. While all TG-TCL responded strongly to the control mitogen PHA-P, demonstrating their ability to secrete IFNγ, only 2 of 10 TG-TCL showed VZV-protein specific CD8 T-cell reactivity: the TG-TCL of subject TG04 and TG07 responded to VZV ORF29 and ORF9, respectively (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We then assayed the respective short-term TG-TCL for IFNγ secretion in response to incubation with the HLA-I matched aAPC. We have previously applied this platform to uncover the targets and diversity of HSV- and VZV-specific T-cells in human blood and other tissues in an unbiased way [ 16 , 19 , 25 27 ]. While all TG-TCL responded strongly to the control mitogen PHA-P, demonstrating their ability to secrete IFNγ, only 2 of 10 TG-TCL showed VZV-protein specific CD8 T-cell reactivity: the TG-TCL of subject TG04 and TG07 responded to VZV ORF29 and ORF9, respectively (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…These impressive results were achieved using only a single immunogen, gD2. Adding other immunogens, particularly immediate early, tegument, and/or capsid proteins that act as effective T cell antigens, may further enhance the efficacy of a therapeutic vaccine [ 14 , 15 , 16 , 17 , 18 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Achieving the goal of outperforming acyclovir/valacyclovir will likely require the selection of immunogens and adjuvants that stimulate potent T cell responses [ 14 , 15 , 16 , 17 , 18 , 19 ]. Herein, we describe immune responses and outcomes using a novel adjuvant, S-540956, developed by Shionogi & Co., Ltd. (Osaka, Japan).…”
Section: Introductionmentioning
confidence: 99%
“…In 2001, Koelle et al studied virus-specific T cell responses from genital lesions of 3 patients and found that the most common responses were to tegument proteins UL47, UL49, and ICP0 ( 27 ). A follow-up study of genital tissue from 8 patients found that the most T cell common responses were to gD (6 patients), gB and UL39 (4 patients), and UL23 (the viral thymidine kinase, 3 patients) ( 28 ).…”
Section: Importance Of Location Of Virus-specific T Cells In Hsvmentioning
confidence: 99%